Effect of (+)-dehydrofukinone on GABAA receptors and stress response in fish model - Garlet,Q.I. (2016)
(+)-Dehydrofukinone (DHF) is a major component of the essential oil of Nectandra grandiflora (Lauraceae), and exerts a depressant effect on the central nervous system of fish. However, the neuronal mechanism underlying DHF action remains unknown. This study aimed to investigate the action of DHF on GABAA receptors using a silver catfish (Rhamdia quelen) model. Additionally, we investigated the effect of DHF exposure on stress-induced cortisol modulation. Chemical identification was performed using gas chromatography-mass spectrometry and purity was evaluated using gas chromatography with a flame ionization detector. To an aquarium, we applied between 2.5 and 50 mg/L DHF diluted in ethanol, in combination with 42.7 mg/L diazepam. DHF within the range of 10-20 mg/L acted collaboratively in combination with diazepam, but the sedative action of DHF was reversed by 3 mg/L flumazenil. Additionally, fish exposed for 24 h to 2.5-20 mg/L DHF showed no side effects and there was sustained sedation during the first 12 h of drug exposure with 10-20 mg/L DHF. DHF pretreatment did not increase plasma cortisol levels in fish subjected to a stress protocol. Moreover, the stress-induced cortisol peak was absent following pretreatment with 20 mg/L DHF. DHF proved to be a relatively safe sedative or anesthetic, which interacts with GABAergic and cortisol pathways in fish.